Chỉ số quản trị công ty và hiệu quả tài chính: Bằng chứng từ Việt Nam - Hồ Việt, Tiến; Nguyễn Đình, Khôi (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
This paper attempts to examine the effects of Corporate Governance Index on financial performance of listed companies on Hochiminh Stock Exchange with the raw data gathered from their annual financial statements and other reports during three years, 2013–2015. Regression models are formulated using five independent variables of five component indexes of Corporate Governance Index and three dependent variables to proxy for Corporate Financial Performance and stability. The results show that there exists a positive relationship between Corporate Governance Index and Corporate Financial Performance  in the same year, but this relationship becomes insignificant considering different years. Particularly, the component indexes of Corporate Governance Index, such as “Equal treatment of shareholders,” “The role of stakeholders,” and “Disclosure and transparency” are crucial factors to the improvement and enhancement of the financial performance of those listed companies in the same year. Meanwhile, “Equal treatment of shareholders” positively affects Tobin’s Q and reduces market risk in the next year.
Keywords: Corporate governance index; OECD principles; Corporate financial performance; Vietnam